Disaster knowledge, preparedness, and risk reduction: a comparative study of education and health students - Alamsyah, Risky; Fai’izah, Lailatul; Kurniawan, Muchammad Akbar; Amin, Saiful (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3618, 2025)
Positioned as liaisons, future teachers and nurses turn disaster theory into community practice. This study aims to compare the knowledge level, preparedness, and disaster risk reduction between education students and health students.. The research approach uses quantitative methods with surveys as a data collection technique. The sample consisted of 84 students of the Social Studies Education Study Program of UIN Maulana Malik Ibrahim Malang and 93 students of the Nursing Study Program of Kepanjen University who were selected using the Slovin formula with an error rate of 5%. The research instruments included a four-point Likert scale questionnaire to measure disaster preparedness and risk reduction, as well as a multiple-choice test to assess disaster knowledge. The data was analyzed using percentage descriptive statistics. The results of the study showed differences between the two groups. Education students obtained the highest average scores in the aspect of disaster knowledge, while health students excelled in the aspects of disaster preparedness and risk reduction. These findings indicate that education students are superior in mastering theoretical concepts of disasters, while health students have better preparedness and practical skills in handling disaster situations because health students are more focused on practice than education students who are more theoretical. The next study is suggested to review differences based on gender and add variables of field experience and educational institution support in improving students' disaster preparedness.